2021
DOI: 10.1252/jcej.20we136
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity for Polymer Composite Materials: Recent Advances in Polyimide Materials

Abstract: Polymer materials have received much attention from a wide range of industrial interests. Functional llers are often introduced to polymers to add new functions that the pristine polymer materials show inferior values. As for thermal conductivity (TC), thermal conductive llers such as ceramics, functional nanocarbons, and metals are often used. Among the polymers used in industrial elds, polyimide (PI) has excellent thermal stability and solvent resistance. However, the TC of PI is low as is often the case in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Polyimide (PI) is a promising engineering plastic with excellent insulation properties, good mechanical strength, and high heat resistance. [9][10][11][12][13] However, it exhibits a low thermal conductivity (TC). To overcome this limitation, fillers with high TC, such as ceramics [14][15][16] and carbon fillers, [17][18][19] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimide (PI) is a promising engineering plastic with excellent insulation properties, good mechanical strength, and high heat resistance. [9][10][11][12][13] However, it exhibits a low thermal conductivity (TC). To overcome this limitation, fillers with high TC, such as ceramics [14][15][16] and carbon fillers, [17][18][19] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have shown prominent levels of electrical insulation and heat resistance. Moreover, polyimide (PI) has also demonstrated excellent levels of electrical insulation and heat resistance, and many studies on the k of PI‐based composites have been reported 12 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polyimide (PI) has also demonstrated excellent levels of electrical insulation and heat resistance, and many studies on the k of PI-based composites have been reported. 12 In filler/polymer composites, a high content of fillers is generally required to achieve a remarkable increment of k. However, a high content of fillers sometimes deteriorates particular polymer properties such as flexibility. Therefore, the use of smaller amounts of fillers to enhance k is generally desirable.…”
Section: Introductionmentioning
confidence: 99%